2005
DOI: 10.1073/pnas.0507385102
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X receptor ablation in adult mouse keratinocytes generates an atopic dermatitis triggered by thymic stromal lymphopoietin

Abstract: To investigate the role of retinoid X receptors (RXRs) in epidermal homeostasis, we generated RXR␣␤ ep؊/؊ somatic mutants in which both RXR␣ and RXR␤ are selectively ablated in epidermal keratinocytes of adult mice. These mice develop a chronic dermatitis mimicking that observed in atopic dermatitis (AD) patients. In addition, they exhibit immunological abnormalities including elevated serum levels of IgE and IgG, associated with blood and tissue eosinophilia, indicating that keratinocyte-selective ablation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
208
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 203 publications
(224 citation statements)
references
References 46 publications
15
208
1
Order By: Relevance
“…This disease development is accompanied by increased TSLP expression in the epidermis, suggesting that RXRs are involved in repressing transcription of the TSLP gene. Consistent with this, they found two nuclear receptor binding sites in the mouse TSLP gene promoter (22). RXRs function as binding partners for a wide variety of nuclear receptors, including members of the retinoic acid receptor family (28,29) and the vitamin D receptor (30) and can act as either transcriptional activators or repressors, depending on the binding partner and the presence or absence of ligands (31)(32)(33).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This disease development is accompanied by increased TSLP expression in the epidermis, suggesting that RXRs are involved in repressing transcription of the TSLP gene. Consistent with this, they found two nuclear receptor binding sites in the mouse TSLP gene promoter (22). RXRs function as binding partners for a wide variety of nuclear receptors, including members of the retinoic acid receptor family (28,29) and the vitamin D receptor (30) and can act as either transcriptional activators or repressors, depending on the binding partner and the presence or absence of ligands (31)(32)(33).…”
Section: Discussionmentioning
confidence: 58%
“…Previous work has shown that epidermal ablation of the nuclear receptors Retinoid X receptor (RXR)␣ and RXR␤ resulted in development of an atopic dermatitis-like disease that included elevated expression of TSLP (22). These authors also identified two possible RXR binding sites upstream of the TSLP gene (base pairs Ϫ1049 to Ϫ1062 and base pairs Ϫ2164 to Ϫ2175).…”
Section: Engagement Of Tlrs On Nhbe Cells Induces Human Tslp Expressionmentioning
confidence: 99%
“…Systemic abnormalities, including elevated serum IgE and IgG levels, associated with blood and tissue eosinophilia, have been observed in RXR␣␤ epϪ/Ϫ and K14-TSLP mice, exhibiting similarities to those observed in AD patients (3). Serum IgE and IgG levels were increased in mice to which MC903 was topically applied for 16 At day 17 of MC903 treatment, an inflammation was obvious on ears of VDR CT mice, whereas VDR epϪ/Ϫ ears did not show any sign of inflammation ( Fig.…”
Section: Topical Application Of Mc903 Triggers An Ad-like Syndromementioning
confidence: 68%
“…Because RXR͞NR heterodimers in which an agonistic ligand is not bound to the NR partner can act as transcriptional repressors (10), we examined whether TSLP expression could be induced by NR agonists. Four nanomoles of ligands were topically applied to whole ears of WT mice for 4 consecutive days (days [1][2][3][4], and TSLP RNA levels were determined on day 5. Application of 1␣,25-(OH) 2 D 3 (the physiologically active vitamin D3) led to a dramatic increase (Ͼ300-fold) in TSLP transcripts at day 5, whereas they were modestly but significantly increased (5-fold) upon application of a RAR␥-selective agonist (BMS961) (11) (Fig.…”
Section: Topical Application Of 1␣25-(oh)2d3 or Its Low-calcemic Analogmentioning
confidence: 99%
See 1 more Smart Citation